Combining Blink, Pupil, and Response Time Measures in a Concealed Knowledge Test - Seymour, Travis; Baker, Christopher A.; Gaunt, Josh T. (Frontiers in Psychology, 2013)
The response time (RT) based Concealed Knowledge Test (CKT) has been shown to accurately detect participants’ knowledge of mock-crime related information. Tests based on ocular measures such as pupil size and blink rate have sometimes resulted in poor classification, or lacked detailed classification analyses. The present study examines the fitness of multiple pupil and blink related responses in the CKT paradigm. To maximize classification efficiency, participants’ concealed knowledge was assessed using both individual test measures and combinations of test measures. Results show that individual pupil-size, pupil-slope, and pre-response blink-rate measures produce efficient classifications. Combining pupil and blink measures yielded more accuracy classifications than individual ocular measures. Although RT-based tests proved efficient, combining RT with ocular measures had little incremental benefit. It is argued that covertly assessing ocular measures during RT-based tests may guard against effective countermeasure use in applied settings. A compound classification procedure was used to categorize individual participants and yielded high hit rates and low false-alarm rates without the need for adjustments between test paradigms or subject populations. We conclude that with appropriate test paradigms and classification analyses, ocular measures may prove as effective as other indices, though additional research is needed.